Development of E-LKPD Biotechnology Banana Yoghurt for Person and Product Creativity Students Phase E - Bellamerna Nurandari; Evy Yulianti (Unnes Science Education Journal, 2025)
This study aims to determine the level of validity and practicality of E-LKPD; the effectiveness of E-LKPD; and the relationship between person and product dimensions of creativity in the experimental class. The research method used is RnD with a 4-D model. The research design used is a quasi-experimental design with a posttest-only design with nonequivalent groups. The study was conducted in one of the schools in Yogyakarta with a small-scale subject of 33 students and a large-scale of 71 students. Data collection techniques used interviews, observations, and questionnaires. The instruments used include questionnaires on learning experiences, materials, media, validation, practitioners, and students; questionnaires on person and product dimensions assessment; and learning implementation. The analysis techniques used are PERMANOVA, Independent Samples T-Test, Mann-Whitney U, and Spearman correlation. Based on the results of the research, the conclusion is E-LKPD has a high-very high level of validity according to experts and the level of practicality of students shows good results. The effectiveness of the product shows a PERMANOVA value of 0.0003 which indicates that there are simultaneous differences in both dimensions in the control and experimental classes; shows a difference in the person dimension with the Mann-Whitney U value and the product dimension of the practicum report with the Independent Samples T-Test value of 0.002; shows a significant relationship of 0.001 with a correlation coefficient of 0.515 which means a strong and positive relationship.